Composite Coagulant (PACSPP) Ability to Remove Ammonia and Colour from Stabilised Leachate Under Ratio, pH and Dosage Influence - Mohamad Yusri, Norbalqis Mayangsari; Mohd Zin, Nur Shaylinda; Zainal Abidin, Nur Natasya; Mohamad Zailani, Laila Wahidah (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Along with chemical coagulants, coagulation-flocculation is one of the applications that works well for stable leachate treatment. Polyaluminium chloride (PAC) and sweet potato peels (SPP) were operated as a composite coagulant (PACSPP) to investigate the efficiency of removing colour and ammonia from Simpang Renggam landfill’s leachate. From the analysis of the results, the optimum ratio of composite coagulant was PACSPP(b) with a 4:6 ratio. The optimum dose and pH for composite coagulant of PACSPP(b) was 5,000 mg/L at pH 6, with removal percentages of colour and ammonia being 92% and 66%, respectively. The removal percentage of colour and ammonia of composite coagulant is at par but with less chemical coagulant. These results show that a composite coagulant made up of chemical coagulant (PAC) and natural coagulant (SPP) combined the best qualities of both coagulants and improved the coagulation effectiveness